Reimagining gendered community interventions: the case of family planning programs in rural Bangladesh - Bhanu Bhatia; Sarah Hossain; Upasona Ghosh; Fanny Salignac (BMC, 2024)
Abstract Family planning programs in Bangladesh have been successfully operating for over half a century, achieving phenomenal reductions in fertility rates. Acknowledging restrictions on women's freedoms, much of the initial program design was concentrated on giving household supplies for women priority. However, one unfortunate impact of these outreach services is that, by bypassing the opportunity to challenge patriarchal attitudes directly, they inadvertently reinforce the power relationships of the status quo. Hence, we problematise the decision-making structures within Bangladesh's family planning programs. We argue that the fundamental flaw with Bangladesh's family planning program is the lack of conscious effort to understand women's health choices and decision-making as a complex contextual process of relational, structural, and institutional forces. Additionally, avoiding men in these programs often creates new dependencies for women, as this approach does not directly seek to build relational bridges based on equality between genders. As a result, many women still depend on permission from their husbands and family for reproductive health services and face constrained family planning choices and access to care. We recommend that family planning programs adopt a broader vision to create new and more sustainable possibilities in an ever-evolving social relations landscape where gender is constantly negotiated. Such strategies are even more pressing in the post-Covid world, as national systems are exposed to uncertainty and ambiguity.